2000
DOI: 10.1046/j.1540-8175.2000.00547.x
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Apical Thrombus and Myocardial Viability: A Dobutamine Stress Echocardiographic Study

Abstract: The objective of this article was to determine whether the presence of left ventricular apical thrombus is a marker of nonviable myocardium. Reduced coronary blood flow secondary to atherosclerosis may result in chronic reversible left ventricular wall-motion abnormalities. Severe regional abnormalities also predispose to formation of left ventricular thrombus. The relationship between left ventricular apical thrombus and myocardial viability has not been previously described. Eighty patients with coronary art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Left ventricular wall motion abnormality (LVWMA) has been suggested as a low or an uncertain risk factor in terms of cerebral embolic risk [ 42 ]. LVWMA is associated with regional blood stasis and incomplete ventricular emptying, which may increase thrombogenicity and induce intraventricular thrombus formation [ 43 - 45 ]. However, as LVWMA may be an epiphenomenon of underlying cardiac diseases, such as myocardial infarction or dilated cardiomyopathy, it is difficult to evaluate the risk of stroke for LVWMA itself.…”
Section: Relationship Between Hf and Neurologic Diseasesmentioning
confidence: 99%
“…Left ventricular wall motion abnormality (LVWMA) has been suggested as a low or an uncertain risk factor in terms of cerebral embolic risk [ 42 ]. LVWMA is associated with regional blood stasis and incomplete ventricular emptying, which may increase thrombogenicity and induce intraventricular thrombus formation [ 43 - 45 ]. However, as LVWMA may be an epiphenomenon of underlying cardiac diseases, such as myocardial infarction or dilated cardiomyopathy, it is difficult to evaluate the risk of stroke for LVWMA itself.…”
Section: Relationship Between Hf and Neurologic Diseasesmentioning
confidence: 99%
“…In agreement with our study, Cusick et al reported no complications during moderate dobutamine stress echocardiography in 55 LV thrombus patients. However, the study fails to achieve an adequately high heart rate response (peak heart rate 114/min) and does not include postprocedural observations or outcome [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that wall thinning is associated with the loss of viable myocardial tissue and fibrosis 28,29 .…”
Section: Discussionmentioning
confidence: 99%